Dispensation for underage marriage: a legal analysis and its implications for adolescent reproductive health in indonesia - RA. Sri Hardini; Agustinus Giri Respati; RM. Achmad Roeswandi; Marsudi Dedi Putra; Carolina Kuntardjo (Science Midwifery, 2026)
Child marriage, facilitated through judicial marriage dispensation mechanisms, constitutes a persistent public health and human rights crisis in Indonesia. Despite the enactment of Law No. 16 of 2019, which raised the minimum marriage age for women from 16 to 19 years, dispensation applications surged by approximately 171% between 2018 and 2020—from 23,700 to 64,211 cases—revealing a profound policy paradox. This study employs a normative juridical method with statute, conceptual, and case approaches to systematically analyze the adequacy of Indonesia's legal framework governing marriage dispensation in protecting adolescent reproductive health. The analysis reveals three compounding structural deficiencies: (1) normative inadequacy of Supreme Court Regulation (PERMA) No. 5 of 2019, which mandates health considerations without prescribing enforceable standards; (2) pervasive legal pluralism that subordinates child protection norms to customary and religious considerations; and (3) the absence of an interdisciplinary adjudicative framework integrating reproductive health evidence into judicial decision-making. Findings from five Religious Court jurisdictions demonstrate that premarital pregnancy dominates as the grant rationale (averaging 68.2% of cases), while substantive health consideration occurs in fewer than 7% of decisions. Provinces with the highest dispensation rates—including South Kalimantan and West Sulawesi—simultaneously record maternal mortality ratios and adolescent anemia prevalence significantly above national averages, indicating a structurally mediated relationship between legal permissiveness and reproductive health burden. This study proposes a four-dimensional health-responsive legal reform framework encompassing: legislative amendment of Article 7(2), mandatory health screening protocols in PERMA revision, judicial capacity building, and harmonization with CRC and CEDAW obligations.